Biological interaction of bioactive polymeric membranes in induced bone defects in rabbit tibias. - Olicies da Cunha; Cássio Ricardo Auada Ferrigno; Solimar Dutra da Silveira; Bruno Gregnanin Pedron; Danielle Tiemi Komorizono; Flávia Cristina Rosin Prado; Walter Israel Rojas Cabrera; Luciana Corrêa (PLoS ONE)
The study aimed to evaluate bone repair using three osteoinductive polymers in bone defects created in rabbit tibias. Forty-eight adult rabbits were assessed at various time points: three, seven, fourteen, and thirty days. The groups included a control group (without biomaterial), M1 (Poly L Lactide co Polycaprolactone/Polyethylene Glycol), M2 (Poly L Lactide co Polycaprolactone/Polyethylene Glycol/β-Tricalcium Phosphate), and M3 (Poly L Lactide co Polycaprolactone/Polyethylene Glycol/nano hydroxyapatite). Histomorphometric analysis was conducted to evaluate new bone formation within and around the bone defect. At 14 (p<0.05) and 30 days (p<0.05), the callus area in the membrane groups, particularly in M3, was also significantly larger than in the control group, indicating the osteoinductive potential of these biomaterials. The callus consisted of both bone and cartilaginous matrix, suggesting a robust activation of endochondral ossification. The number of osteoclast was higher in the membrane groups, especially at 14 days in the M3 group, indicating increased bone remodeling activity. The membranes were not fully absorbed by 30 days, creating a space between the defect and the periosteum. In conclusion, all three membranes showed significant chondro and osteoinductive potential, with the membrane containing nano-hydroxyapatite demonstrating the most pronounced potential.